Experimental and numerical study on seismic performance of CLB rocking wall with bending-friction coupled dampers. (January 2022) - Lu, Yujie; Lv, Qingfang; Liu, Ye
Abstract: As a sustainable constructional material, the cross-laminated bamboo (CLB) has high strength and close mechanical properties in the two directions and is suitable for the construction of high-rise buildings. In the present study, a novel CLB rocking wall structure installed with bending-friction coupled damper (BFCD) that was designed by combining the conventional friction damper (CFD) and bending bars was proposed and tested under quasi-static tests. The effect of the loading protocol, the friction force provided by dampers, the damper type and the type of bending bars on the seismic performance of the CLB rocking wall was discussed. Test results showed that the CLB rocking wall structure with BFCDs had a typical flag-shaped hysteretic curve and could sustain secondary loading with little structural damage and strength loss. The cumulative energy dissipation increased with the increase of friction force while the relative self-centering efficiency reduced. The CLB rocking wall with BFCDs had a better energy dissipation capacity than that with CFDs due to the contribution of the additional energy dissipation provided by bending bars. Besides, the partially weakened bending bar was found to dissipate more energy than the linear bending bar. The stress distribution of the CLB rocking wall was further discussed based on a validated finite element model. The research achievements of this study are expected to fill the research gap of the CLB rocking wall and promote the development of high-rise bamboo structures. Highlights: Proposal of a CLB rocking wall structure with bending-friction coupled dampers. Quasi-static tests of CLB rocking walls with BFCDs based on 10 cases. Numerical analyses on the stress distribution of the CLB rocking wall.